THE EFFECTS OF BRAND AMBASSADOR, SOCIAL MEDIA MARKETING, AND ADVERTISING CAMPAIGN OF SOMETHINC PRODUCT ON PURCHASE INTENTION: (Study On Somethinc Users in Medan City) - Azzuhra, Annisa; Adlina, Hafiza (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The increasing awareness within the community regarding the significance of skincare, especially for the face, has led to a high demand for facial care products, resulting in the emergence of numerous new skincare brands in the market. Among these brands, Somethinc has gained prominence, particularly in Medan City, where it secured the top position in skincare sales on e-commerce platforms in 2022. This research aims to investigate the impact of brand ambassadors, social media marketing, and advertising campaigns for Somethinc products on purchase intention within the Medan City community. The study employs a quantitative research approach with an associative methodology and utilizes SPSS software for data analysis. The research population comprises all members of the community in Medan City who use Somethinc, with a total of 100 respondents as the sample. The findings indicate that the brand ambassador variable has a negative and statistically insignificant effect on purchase intention, while the variables of social media marketing and advertising campaigns have a positive and statistically significant impact. The F-test results reveal that all three independent variables collectively influence the purchase intention of Somethinc products within the Medan City community, explaining 64.9% of the variance.